QuiZtudy: An implementation of a Quiz System with Activity Log - Abdullah, Nur Farah Hani; Rahim, Nordiana (Applied Information Technology And Computer Science, 2021)
Quiz system is a web-based quiz system for accessing students in teaching and learning. Conservative methods in teaching and learning are not suitable as the Covid-19 pandemic hits global, and schools need to be closed. Hence, school and university need to adapt online distance learning throughout this pandemic. Nowadays, online quiz system is used all around the world. However, some of the existed quiz system does not allow teachers to have a view on students that do not login into the quiz system during the quiz session is held. QuiZtudy will provide a platform for students and lecturer to create one of teaching and learning method effectively without need to have face-to-face learning. It requires teachers to create quiz and student to answer the quiz according to their respective teacher. This system also will implement activity log that will keep track on the action of users as one of the purposes of the activity log is to measure the activity done by users in the system. Users need to login into the system to use the functions in the system. Methodology used in QuiZtudy development is Waterfall. As a result, the system managed to display activity log where each modification on registration is stated in the system. there is also login history where administrator can know users that logged into the system with the time.